Review paper Changing concepts on prostatitis - Prezioso, Dominic; Naber, Kurt G.; Lobel, Bernard; Weidner, Wolfgang; Algaba, Feran; Denis, Louis J.; Griffiths, Keith (Archives of Medical Science, 2006)
Comparatively little research has been directed to the pathogenesis and treatment of prostatitis, an infectious, inflammatory disabling condition that can cause considerable pelvic pain, with a range of associated symptoms that can influence 50% of all men at some period in their lives, often in their earlier adult years. This review considers the impact of prostatitis on patients and highlights the clear need for clinical research to enhance our understanding of the underlying biology of this ubiquitous disease. New insights into the molecular events that may be implicated in its pathogenesis, suggest that more rational treatment options could well be developed, but throughout, there is the recognition that prostatitis still remains an enigma.